Needs and Challenges of Seniors with Combined Hearing and Vision Loss. (November 2016) - McDonnall, Michele C.; Crudden, Adele; LeJeune, B. J.; Steverson, Anne; O'Donnell, Nancy
Introduction: The purpose of this study was to identify the needs and challenges of seniors with dual sensory loss (combined hearing and vision loss) and to determine priorities for training family members, community service providers, and professionals who work with them. Methods: Individuals (N = 131) with dual sensory loss between the ages of 55 and 99 years participated in a survey designed to collect information about their most important needs, challenges encountered associated with sensory losses, and the training requirements of the people who interact with them. Results were analyzed with descriptive statistics, and comparisons were made between persons with early and late onset of sensory loss. Results: The most commonly identified needs were transportation, technology training, assistance with errands, and improved communication. Medical providers were identified as the service providers who most need training about dual sensory loss. A majority of respondents thought their local community members, friends, and family also need education. Some differences were noted based on age of onset of sensory losses. Discussion: Needs differed by age of onset group: needs of participants with early onset of one or both sensory losses focused on transportation and training to use technology, while needs for those with later onset focused on information about devices to improve hearing or vision and better ability to communicate with family. Implications for practitioners: Training to use technology is an important area of need that may not always be addressed for this population by service providers, but it may contribute to overall improved quality of life, since it has the potential to improve communication options and reduce feelings of isolation. Health care providers are an important group to target for education regarding how to interact with people with dual sensory loss.